Perancangan Aplikasi Digital untuk Optimalisasi Layanan Pengiriman Barang di Himeji Express Banjarmasin - Fakhriani Ekawati; Yusup Indra Wijaya; Muharir Muharir (Journal Islamic Global Network for Information Technology and Entrepreneurship, 2025)
The advancement of digital technology has driven many service companies to transform toward faster, more efficient, and accurate systems. Himeji Express Banjarmasin, a company engaged in the field of goods delivery services, still faces challenges in data management and service processes that are mostly carried out manually. This condition leads to delays in shipment tracking, data entry errors, and limitations in report generation. To address these issues, a digital application was designed to optimize the delivery service processes at Himeji Express Banjarmasin. The application was developed using the Unified Modeling Language (UML) approach to model system requirements through use case, activity, sequence, and class diagrams. The implementation process utilized Sublime Text and XAMPP software, supported by an integrated database. The results show that the developed digital application can improve the effectiveness of managing customer, employee, pricing, cargo, and transaction data while generating automatic and real-time reports. This application enhances operational efficiency, transparency, and responsiveness to customer needs at Himeji Express.